Literature study: Use of Sungkai leaf and Virgin Coconut Oil (VCO) in soap making - Astuti, Syurmi; Sunarsih, Elvi (Goodwood Publishing, 2024)
Purpose: This literature review discusses using Sungkai leaves (Peronema canescens Jack) and Virgin Coconut Oil (VCO) in soap production as promising natural alternatives in the cosmetic industry. Sungkai leaves have been proven to possess antibacterial, anti-inflammatory, and antioxidant activities, while VCO is known for its antimicrobial and anti-inflammatory properties. Method: The research method employed in this study is a literature review, which gathers, analyzes, and synthesizes information from various literature sources to present a comprehensive overview of the use of both ingredients in soap production. Results: The research results indicate that the combination of Sungkai leaves and VCO in soap provides good cleansing effects and maintains the skin's health and moisture. The practical implications of this research are the potential development of more effective and environmentally friendly soap products in the cosmetic industry. Conclusion: The combination of Sungkai leaves and VCO can serve as an effective natural soap formulation with considerable health and cosmetic benefits. Their application supports sustainable and eco-friendly practices in the personal care industry. Limitations: This study is limited to secondary data and does not involve laboratory testing or clinical trials. Variations in extraction methods and formulations among reviewed studies may affect generalizability. Contribution: This review contributes to the growing body of knowledge on natural cosmetics by providing scientific support for the development of herbal soaps. It promotes the use of local natural resources in cosmetic innovation and encourages further research and product development based on Sungkai and VCO.